Bromide-bromate Couple of Varying Ratios for Bromination, Vicinal Functionalisation and Oxidation in a Clean Manner - Adimurthy, Subbarayappa; C. Ranu, Brindaban; Ramachandraiah, Gadde; Ganguly, Bishwajit; K. Ghosh, Pushpito (Current Organic Synthesis, 2013)
The review highlights applications of bromide-bromate couple in organic synthesis. The couple having 5:1 mole ratio of bromide to bromate is useful for preparation of dibromo derivatives from alkenes/alkynes. The 2:1 couple affects substitution with high bromine atom efficiency. Vicinal functionalization of olefins has also been studied. The 1:8 bromide-bromate couple has proved promising in several oxidation reactions, the performance exceeding that of bromate alone. This reagent was also the most effective for deiodination of styrene-based iodohydrins with concomitant rearrangement by a novel pathway. In all the cases the reagents were activated through in situ acidification. The 5:1 reagent is obtained as intermediate during liquid bromine manufacture and the other reagents were prepared from it using ClO-. Liquid bromine could be avoided in the product life cycle.
Keywords: direct preparation from bromine intermediate